2017
DOI: 10.17159/sajs.2017/20160105
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of vumba and ubumba clays used for cosmetic purposes

Abstract: HOW TO CITE:Morekhure-Mphahlele R, Focke WW, Grote W. Characterisation of vumba and ubumba clays used for cosmetic purposes. S Afr J Sci. 2017;113(3/4) FUNDING:Tshwane University of Technology Two traditional cosmetic clays bear similar names in different local South African languages: vumba (Tshivenda) and ubumba (isiZulu). The wet clays are applied topically for cosmetic purposes by the respective indigenous peoples. Six samples from two South African provinces were characterised using X-ray diffraction, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…[29][30][31] In addition, the loss of ignition (12.55 %) is in agreement with the results reported elsewhere for clay deposits sampled from KwaZulu-Natal and Limpopo provinces of South Africa. 32 The loss of ignition is attributed to organic matter and the value obtained in this study is coherent with kaolinite rich clay, for which 13-14 % loss of ignition is known as a mean value. 33,34 …”
Section: Chemical Composition Of the Raw Claysupporting
confidence: 79%
“…[29][30][31] In addition, the loss of ignition (12.55 %) is in agreement with the results reported elsewhere for clay deposits sampled from KwaZulu-Natal and Limpopo provinces of South Africa. 32 The loss of ignition is attributed to organic matter and the value obtained in this study is coherent with kaolinite rich clay, for which 13-14 % loss of ignition is known as a mean value. 33,34 …”
Section: Chemical Composition Of the Raw Claysupporting
confidence: 79%
“…This was in agreement with the results reported by Madikizela et al The GOL sample exhibited the lowest mass loss (8.33 wt %) compared to the other two samples, namely, KAT (12.59 wt %) and KOL (12.04 wt %), implying that GOL contains fewer organic constituents. Furthermore, it has been reported that mass losses are often associated with the oxidation of organic constituents present in the materials . Boulingui et al have also reported that there are major reactions involving loss of H 2 O, CO 2 , and/or organics in clay materials.…”
Section: Resultsmentioning
confidence: 99%
“…In some part of the world, including the African continent, clays are used for cosmetic purposes. Morekhure-Mphahlele et al . indicated that some clays in the Eastern Cape in South Africa are used for their moisturizing effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by the participants, it is used for skin protection from sun and insect bites. The cosmeceutical value of ochre has been recorded in several studies [32,33]. In Western Sahara, Volpato et al [34] indicated that Sahrawi refugees apply red ochre around their eyes to reduce solar radiance.…”
Section: Diversity Of Natural Resources Used For Folk Cosmeceuticalsmentioning
confidence: 99%